Antibiotic therapy to prevent the development of asymptomatic middle ear effusion in children with acute otitis media: a meta-analysis of individual patient data. - Koopman, L; Hoes, A; Glasziou, P; Appelman, C; Burke, P; McCormick, D; Damoiseaux, R; Le Saux, N; Rovers, M (2008)
OBJECTIVES: To determine predictors of the development of asymptomatic middle ear effusion (MEE) in children with acute otitis media (AOM) and to assess the effect of antibiotic therapy in preventing the development of MEE in these children. DATA SOURCES: A systematic literature search was performed using PubMed, EMBASE, the Cochrane databases, and the proceedings of international otitis media symposia. STUDY SELECTION: A trial was selected if the allocation of participants to treatment was randomized, children aged 0 to 12 years with AOM were included, the comparison was between antibiotic therapy and placebo or no (antibiotic) treatment, and MEE at 1 month was measured. DATA EXTRACTION: Data from 5 randomized controlled trials were included in the meta-analysis of individual patient data (1328 children aged 6 months to 12 years). We identified independent predictors of the development of asymptomatic MEE and studied whether these children benefited more from antibiotic therapy than children with a lower risk. The primary outcome was MEE (defined as a type B tympanogram) at 1 month. DATA SYNTHESIS: The overall relative risk of antibiotic therapy in preventing the development of asymptomatic MEE after 1 month was 0.9 (95% confidence interval, 0.8-1.0; P =.19). Independent predictors of the development of asymptomatic MEE were age younger than 2 years and recurrent AOM. No statistically significant interaction effects with treatment were found. CONCLUSION: Because of a marginal effect of antibiotic therapy on the development of asymptomatic MEE and the known negative effects of prescribing antibiotics, including the development of antibiotic resistance and adverse effects, we do not recommend prescribing antibiotics to prevent MEE.